Derivation of Postharvest Fruit Behavior Reduced Order Models for Online Monitoring and Control of Quality Parameters During Refrigeration. Issue 4 (7th March 2013) - Rivas, Diana; Vilas, Carlos; Alonso, Antonio A.; Varas, Fernando
Abstract In this paper, an efficient computational tool to predict the evolution of the key variables in the fruit refrigeration process is presented. This computational model is intended to be used in real time quality control. The tool is based on detailed mathematical models proposed in the literature which accounts for the main phenomena occurring during refrigeration. Since integration using standard numerical schemes leads to a computational cost unaffordable in real time environments, a reduced order model (ROM; able to combine a high accuracy with a low computational cost) is derived. In the derivation of this model, the role of the presence of quite disparate time scales is considered. In this respect, two alternative ROMs are considered: a general model (aiming at describing the evolution at arbitrary time scales) and a model assuming a strong coupling between the state variables (as expected in the long term behavior of the system). Practical Applications The modeling reduction methodology proposed in this work for the fruit refrigeration process, either during storage or transport, will enable the use of computer‐aided process engineering tools for reducing the computational load required to perform predictions. With such tools, optimal operation policies to maximize fruit quality, extend the storage time and/or minimize costs can be efficiently obtained. Also, in the event of unexpected disturbances, they will allow us to recompute in real time the operation policy, and in this way ensure a minimum quality lost.